KAJIAN YURIDIS MENGENAI HAKI SEBAGAI JAMINAN UTAMA BERDASARKAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 2022 TENTANG PERATURAN PELAKSANAAN UNDANG UNDANG NOMOR 24 TAHUN 2019 TENTANG EKONOMI KREATIF - DIMAS INDRAYANA; Zaenal Arifin Dilaga (Private Law, 2023)
This study aims to describe, explain the legal arrangements related to intellectual property rights used as collateral for debt in bank and non-bank financial institutions and assess the value of an intellectual property right. This research was carried out using normative legal research methods using a conceptual and statutory approach. The results of the research show that the approach method used to measure the value of an intellectual property that will be used as collateral is the cost approach, market value approach, income approach, and other approaches with intellectual property appraisers who evaluate Intellectual Property according to what is written in Government Regulation Number 24 of 2022 concerning Regulations for Implementing Law Number 24 of 2019 concerning the Creative Economy